2022
DOI: 10.1038/s43018-022-00391-0
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell map of dynamic chromatin landscapes of immune cells in renal cell carcinoma

Abstract: A complete chart of the chromatin regulatory elements of immune cells in patients with cancer and their dynamic behavior is necessary to understand the developmental fates and guide therapeutic strategies. Here, we map the single-cell chromatin landscape of immune cells from blood, normal tumor-adjacent kidney tissue and malignant tissue from patients with early-stage clear cell renal cell carcinoma (ccRCC). We catalog the T cell states dictated by tissue-specific and developmental-stage-specific chromatin acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Although a previous study revealed the regulatory dynamics of immune cells in ccRCC ( 21 ), the regulatory characteristics of tumor cells remain unknown at single-cell level. To investigate the characteristics of chromatin regulation in tumor cells, we identified 16 tumor cell subtypes and the chromatin accessibility regions of each cell subtype by using scATAC-seq ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a previous study revealed the regulatory dynamics of immune cells in ccRCC ( 21 ), the regulatory characteristics of tumor cells remain unknown at single-cell level. To investigate the characteristics of chromatin regulation in tumor cells, we identified 16 tumor cell subtypes and the chromatin accessibility regions of each cell subtype by using scATAC-seq ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has constructed a single-cell map of dynamic chromatin landscapes of immune cells in renal cell carcinoma, which provided a rich resource for understanding the functional states and regulatory dynamics of immune cells in ccRCC (21). However, a more comprehensive single-cell chromatin accessibility landscape of ccRCC with large samples, including tumor cells, needs to be constructed, which may reveal the regulatory characteristics of tumor cells.…”
Section: Construction Of Single-cell Chromatin Accessibility Landscap...mentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently applied the UMAP and t-SNE algorithms on the top 30 principal components to visualize the high dimensional scRNA-seq data and 14 clusters were obtained. Previous canonical cell markers [ 19 , 20 , 21 ] and CellMarker 2.0 [ 22 ] helped us to identify seven T cell subsets ( Figure 1 A,E). Namely, exhausted CD8 + T cells, cytotoxic CD8 + T cells, resident memory CD4 + T cells, cluster1-resident memory CD8 + T cells, cluster2-resident memory CD8 + T cells, CD4 + CD25 + FOXP3 + regulatory T cells, and naive CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Though the immune checkpoint blockade (ICB) therapies are emerging anticancer therapy, the response rate is still variable within and across solid tumour types. To gain insights into this, recent studies have focused on the characterisation of genetic and molecular alterations at the tumour and immune cell levels, and whether these alterations can be used as biomarkers to predict response to ICB therapies (39,41,42). For example, the study by Kalaora et al, (17) showed that the IP gene expression can be used as a potential biomarker to predict prognosis and response to ICB therapy in skin melanoma.…”
Section: Discussionmentioning
confidence: 99%